Evaluation of the sub-acute toxicity of the sclerotium of Lignosus rhinocerus (Cooke), the Tiger Milk mushroom - Lee, S.S.; Tan, N.H.; Fung, S.Y.; Pailoor, J.; Sim, S.M. (2011)
ETHNOPHARMACOLOGICAL RELEVANCE: Lignosus rhinocerus (known locally as 'Tiger Milk mushroom') is the most important medicinal mushroom used by the indigenous communities of Malaysia to treat fever, cough, asthma, cancer, food poisoning and as a general tonic. The sclerotium of the mushroom is the part with medicinal value. Lignosus rhinocerus was hitherto unexploited commercially because of limited supply. Recently, the mushroom was successfully cultivated. MATERIALS AND METHODS: Sprague Dawley rats (5 rats/group/sex) were fed orally with 250, 500 and 1,000 mg/kg TM02, 1,000 mg/kg TM03 as well as 1,000 mg/kg wild type Lignosus rhinocerus sclerotial powder. Sclerotial powder was orally administered once daily and consecutively for 28 days. Body weight of each animal was measured and any gross behavioral change was observed daily. Hematological and clinical biochemical parameters as well as histopathological analysis were carried out on 29th day. RESULTS: The results showed that oral administration of the sclerotial powder at daily dose of up to 1,000 mg/kg had no adverse effect on the growth rate, hematological and clinical biochemical parameters (including renal and liver function parameters). Histological studies showed that the treatments did not induce any pathological changes in the liver, kidney, heart, spleen and lung of the animals. CONCLUSION: In conclusion, our results show that there was no treatment-related sub-acute toxicity in rats following 28-days oral administration of 250, 500 and 1,000 mg/kg TM02, 1,000 mg/kg TM03 as well as 1,000 mg/kg wild type Lignosus rhinocerus sclerotial powder. As the highest tested dose of 1,000 mg/kg was not associated with any toxicity concern, the NOAEL dose is higher than 1,000 mg/kg.